Evaluation of health literacy and medication regimen complexity index among patients with human immunodeficiency virus infection: A single-Centre, prospective, cross-sectional study - Basavaraj Poojar; Ashok Shenoy K; Ashwin Kamath; John Ramapuram; Sathish B. Rao (Elsevier, 2023)
Background: A limited number of studies have explored the association between health literacy (HL) and health outcomes. Effectively managing HIV infection expects from the patients the ability to seek medical help, understand the instructions provided by the healthcare professionals, and adhere to the treatment plans. This study aimed to evaluate the HL and medication regimen complexity index (MRCI) among people living with HIV and determine the associated factors. Methods: This was a prospective, cross-sectional study. Each study participant was assessed using the HIV literacy test (HIV-LT). The complexity of the prescribed drug regimen was measured using MRCI. Changes in HL and MRCI with age, gender, and educational status of the individual were assessed. The presence of any correlation between HL and MRCI scores was assessed using Spearman's correlation coefficient test. Results: Of the 285 patients with HIV infection studied, 51.6% were males and 48.4% were females. The median HIV-LT score was 3 (out of 10) (interquartile range [IQR], 0-6), and the median MRCI score was 8 (6-12). A statistically significant increase in the HL scores based on the educational status of the participants was seen (x2 = 87.324, p < 0.001). Conclusion: Our study reveals that the majority of the HIV-infected patients studied had inadequate HL as measured using the HIV-LT tool. Those with poor HL did not receive more number of drugs as compared with those with higher HL. Strengthening the counselling and supportive care in patients with HIV, particularly among those with poor HL, is necessary. Clinical trial registration: CTRI/2019/06/019609.